Three-Dimensional Physical Similarity Simulation of the Deformation and Failure of a Gas Extraction Surface Well in a Mining Area. (26th October 2020) - Fu, Junhui; Sun, Haitao; Wen, Guangcai; Li, Rifu
Abstract : Surface well deformation and failure in a mining area are a key issue challenging the surface well gas extraction technique. To provide information for the design of gas extraction surface wells in mining areas, the deformation and failure of surface wells with different materials under the influence of mining-induced rock movement were analyzed based on a three-dimensional physical similarity simulation and key strata theory. The research findings reveal that the fractures in the overlying strata had an elliptic-parabolic shape. The stope center was the highest point in the fracture zone. Horizontal shear deformation was most likely to occur in the thick strata (horizontal shear deformation could be larger if they were key strata) with large strength and stiffness near the intersection between the fracture surface of the overlying strata and the surface well. Due to the shear force and bending moment of the key strata, the surface well deformed into an S-shape. In addition, the surface well was vulnerable to shear deformation in the key strata. The surface well deformation did not weaken from bottom to top due to rock movement. Instead, it was subject to the influence of the rupture strength of the key strata. The surface well above the key strata was prone to tensile strain-compressive strain transition. In contrast, an abrupt change in the compressive strain occurred in the surface well below the key strata where tensile failure may occur. Moreover, a mechanical model of the surface well during the movement of the key strata was established according to the characteristics of the surface well deformation. The test results provide important information on the design optimization of surface wells and high-risk area protection in mining areas.